2014
DOI: 10.1097/pcc.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonnutritive Sucking and Oral Stimulation on Feeding Performance in Preterm Infants

Abstract: The combined NNS + OS intervention reduced the transition time from introduction to independent oral feeding and enhanced the milk transfer rate. The combined intervention seems to have a beneficial effect on oral feeding proficiency in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 32 publications
2
37
0
10
Order By: Relevance
“…For example, in preterm infants receiving gavage feeds, oral motor intervention has been shown to increase non-nutritive sucking pressure and activity (Barlow, Finan, Lee, & Chu, 2008; Poore & Barlow, 2009). This resulted in decreased time to achieve full oral feeds (Lessen, 2011), higher milk transfer rates, and greater volume taken during oral feeds (Zhang et al, 2014). Data for reduction in length of stay has been mixed (Bache, Pizon, Jacobs, Vaillant, & Lecomte, 2014; Zhang et al, 2014), though a recent metaanalysis including these studies concluded that length of stay was reduced by a mean of 3.64 days (95% CI, −5.57 to −1.71) (Tian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in preterm infants receiving gavage feeds, oral motor intervention has been shown to increase non-nutritive sucking pressure and activity (Barlow, Finan, Lee, & Chu, 2008; Poore & Barlow, 2009). This resulted in decreased time to achieve full oral feeds (Lessen, 2011), higher milk transfer rates, and greater volume taken during oral feeds (Zhang et al, 2014). Data for reduction in length of stay has been mixed (Bache, Pizon, Jacobs, Vaillant, & Lecomte, 2014; Zhang et al, 2014), though a recent metaanalysis including these studies concluded that length of stay was reduced by a mean of 3.64 days (95% CI, −5.57 to −1.71) (Tian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in decreased time to achieve full oral feeds (Lessen, 2011), higher milk transfer rates, and greater volume taken during oral feeds (Zhang et al, 2014). Data for reduction in length of stay has been mixed (Bache, Pizon, Jacobs, Vaillant, & Lecomte, 2014; Zhang et al, 2014), though a recent metaanalysis including these studies concluded that length of stay was reduced by a mean of 3.64 days (95% CI, −5.57 to −1.71) (Tian et al, 2015). Our study was one of the first to employ oral motor intervention exercises in infants with complex CHD born at or beyond 37 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang 2014 reported on the use of NNS, and NNS and oral stimulation 30 minutes prior to gavage feeding. Infants in the NNS group were allowed to suck on pacifiers for five minutes, 7 to 8 times a day (Zhang 2014). The pacifier was placed in the infant's mouth whether or not they made an attempt to suck; however, where necessary the nurse would manipulate the pacifier to encourage sucking.…”
Section: Nns Before Gavage Feedingmentioning
confidence: 99%
“…The challenge for mothers and low-birth weight newborns, admitted at neonatal intensive care unit (NICU) and fed through orogastric tube is the establishment of breastfeeding, because the beginning of sucking feeding is directly related to lower hospitalization length 13,14 . The lower the breastfeeding time, the higher the possibility of introducing sucking habits 6,15,16 .…”
Section: Introductionmentioning
confidence: 99%